HUMAN RESOURCE MANAGEMENT TRAINING FOR BUMDES MANAGERS TO IMPROVE THE PROFESSIONALISM AND PERFORMANCE OF THE SEUNEUBOK DRIEN VILLAGE ORGANIZATION, KUTA MAKMUR DISTRICT, NORTH ACEH REGENCY - Sutan Febriansyah; Surya Darni; Nasruddin; Intan Maulida; Rozaliana; Rifki (RADJA PUBLIKA, 2025)
Village-Owned Enterprises (BUMDes) are strategic instruments in village economic development, but their management still faces various challenges, particularly in human resource (HR) management. This community service activity aims to improve the capacity of BUMDes managers through HR management training. The methods used included workshops, group discussions, case studies, assistance in developing standard operating procedures (SOPs), simulations, and evaluations. The training results showed an increase in participant understanding, with an average pre-test score of 54 and a post-test score of 82, representing a 51.9% increase. Furthermore, 80% of participants successfully drafted a simple HR management SOP that could be immediately implemented in their respective BUMDes. This activity not only improved the knowledge and skills of managers but also produced a managerial document that serves as a work guideline. Thus, this training was effective in strengthening the professionalism of BUMDes management and contributing to improved village organizational performance.